2014
DOI: 10.1007/s40688-013-0005-3
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Teacher Ratings of Student Literacy to Identify At-Risk Students: an Analysis of Data from the Early Childhood Longitudinal Study

Abstract: The identification of children at-risk for reading problems can be costly and time-consuming. Previous research has indicated that teachers are relatively accurate in assessing children's overall reading ability. This study investigated the accuracy of kindergarten and first grade teacher rating scales in predicting children's reading scores on assessments in kindergarten, first, third, and fifth grades. The sample included 8,806 children from the Early Childhood Longitudinal StudyKindergarten cohort (ECLS-K).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…could guide teachers in their decision-making process. Studies with guided questionnaires have shown that teachers can reliably identify at-risk students (Connor et al, 2013;Titley et al, 2014). Teachers' prior knowledge can influence the diagnostic and intervention process, too (e.g., Piasta et al, 2009).…”
Section: Future Directions In Research and Practical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…could guide teachers in their decision-making process. Studies with guided questionnaires have shown that teachers can reliably identify at-risk students (Connor et al, 2013;Titley et al, 2014). Teachers' prior knowledge can influence the diagnostic and intervention process, too (e.g., Piasta et al, 2009).…”
Section: Future Directions In Research and Practical Implicationsmentioning
confidence: 99%
“…In two studies, preschool teachers rated children's literacy skills on several subcomponents of reading (i.e., letter-sound knowledge, letter-name knowledge). Taken together, these ratings led to the conclusion that teachers were rather good at identifying children at risk for literacy difficulties (Taylor et al, 2000;Titley et al, 2014). Thus, studies focusing on a range of skills that teachers might teach and observe in their students found more positive results.…”
mentioning
confidence: 96%
“…A corresponding example in the Arabic language could be explicitly teaching the suffix ' ‫ان‬ -'meaning 'two' can support readers in discovering the meaning of the word ‫'كوبان'‬ (Saiegh-Haddad, 2013). Furthermore, it has been argued that greater metalinguistic knowledge not only makes it easier for teachers to explicitly teach these skills but it additionally helps teachers identify and respond to students' specific reading difficulties and errors (Schmitterer & Brod, 2021;Titley et al, 2014;Zipke, 2021) as well as increases confidence and literacy teaching self-efficacy (Bos et al, 1999;Carlisle et al, 2011;Fielding-Barnsley & Purdie, 2005;Moats & Foorman, 2003McCutchen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%